147k views
0 votes
I need to get the left side to equal the right side. Keeping the right side alone and not changing it.

I need to get the left side to equal the right side. Keeping the right side alone-example-1

1 Answer

1 vote

To prove the trigonometric equation:


\sin ^(3) x+\cos ^(3) x=(\sin x+\cos x)(1-\sin x \cos x)


RHS=(\sin x+\cos x)(1-\sin x \cos x)

We know that
\sin^2x +\cos^2x=1, substitute this in place of 1.


=(\sin x+\cos x)(\sin^2x +\cos^2x-\sin x \cos x)

Multiply each term of the first term with each term of the 2nd term.


=\sin^3x + \sin x \cos^2x-\sin^2 x \cos x+\cos x \sin^2 x + \cos^3 x-\sin x\cos^2 x

Group like terms together.


=\sin^3x +( \sin x \cos^2x-\sin x\cos^2 x)+(\cos x \sin^2 x-\sin^2 x \cos x) + \cos^3 x


=\sin^3x +( 0)+(0) + \cos^3 x


=\sin^3x + \cos^3 x

= LHS

RHS = LHS


\sin ^(3) x+\cos ^(3) x=(\sin x+\cos x)(1-\sin x \cos x)

Hence proved.

User Fawad
by
5.3k points